Anatomical and Radiological Study of the Greater Palatine Foramen in Adult Human Skulls - Abeer H. Amer , (Scientific Journal of University of Benghazi, 2019)
Thirty adult human skulls with full eruption of the third molar teeth were examined to determine the anatomy of the greater palatine foramen and canal. Forty computerized tomography scans of the patients were collected to study the location of the greater palatine foramen, direction and length of the greater palatine canal. Dry skulls were differentiated into 14 males and 16 females. Bony results demonstrated that the most common location for the greater palatine foramen was opposite the upper third molar tooth. The most common direction for the greater palatine canal into the oral cavity was anteroinferiorly. In radiological results (CT scan): the mean length of the greater palatine canal was 21.7 mm in males; and 18.1 mm females. The most common location of the greater palatine foramen (GPF) was (1) Opposite the third molar in 45% of the males; and 45% of the females. (2) The next common location was between the second and third molar teeth in 25% of the males; and 30% of the females. (3) Then opposed to the second molar in 20% of the males; and in 25% of the females, (4) Distal to the to the third molar in 10% of the males; and non in females. The direction of the greater palatine canal was anteroinferiorly in 55% of the males; and in 65% of the females. It is concluded that the dentist has to take these anatomical notes with consideration to obtain a successful injection for greater palatine nerve block.